International law and the legal history of Malaysia: an analysis of the sovereign status of the Malay states in the colonial era - Ahamat, Haniff (2013)
This paper looks at how international law informs the sovereign status of the polities that form Malaysia and how such status impacted on the formation of the State. Malaysia as an independent State did not emerge out of colonialism from a single entity. Malaya which gained independence in 1957 and later Malaysia which was formed in 1963 came into being as a result of several States agreeing to form a federation. These States were historically sovereign or part of sovereign Sultanates. This paper will analyse various treaties entered into by these States, the British and other Powers that had an effect on the sovereignty of the Malay States. This paper hypothesizes that under international law, transfer of sovereignty to the British had taken place despite the choice of protectorates by the British for the Malay States. This paper finds that there was no total loss of sovereignty by the Malay States as the Malay Rulers were recognized as sovereign in the British courts of law and they maintained exclusive control over Islam and the Malay custom. However, as international law was heavily influenced by positivism at the peak of European colonization of Asia and Africa, it is not possible for the residual sovereignty to be defended. At the same time the protectorate treaties had consolidated the power of the Sultan within his respective State ending the practice of decentralized rule inherited from the Hindu concept of mandala.